The Collecting History of the Vélez Blanco Patio: Unpublished Documents and New Photographs (BSAA arte, 2019)
The article focuses on the decisions and events that brought an important work of Spanish Renaissance architecture from Spain to the U.S.: the Vélez Blanco patio, today installed outside the entrance to the Thomas J. Watson Library at the Metropolitan Museum of Art, New York. Commissioned at the beginning of the 16th century by Pedro Fajardo y Chacón, the imposing structure was sold in 1904 by its legitimate owners to the dealer J. Goldberg. Subsequently, its marbles were shipped from Andalusia to Paris and, a few years later, to Manhattan, where it was installed in the Park Avenue house built by the banker George Blumenthal. Now, numerous new archival documents, together with unpublished photographs, allow us to accurately reconstruct the different phases of this complex history. In particular, they clarify the chronology of and the actors involved in the successive phases that brought the work across the Atlantic, up until it joined the collections of the Met during the Fourties.
Keywords: Renaissance; Vélez Blanco; Collecting; Spanish heritage; Dukes of Medina Sidonia; Photography; Jacques Seligmann; Raoul Heilbronner; George Blumenthal; Mattie Edwards Hewitt